Situating Ontario’s Colleges Between the American and European Models for Providing Opportunity for the Attainment of Baccalaureate Degrees in Applied Fields of Study - Skolnik, Michael (Canadian Journal of Higher Education, 2016)
During the last third of the twentieth century, college sectors in many countries took on the role of expanding opportunities for baccalaureate degree attainment in applied fields of study. In many European countries, colleges came to constitute a parallel higher education sector that offered degree programs of an applied nature in contrast to the more academically oriented programs of the traditional university sector. Other jurisdictions, including some Canadian ones, followed the American approach, in which colleges facilitate degree attainment for students in occupational programs through transfer arrangements with universities. This article offers some possible reasons why the Ontario Government has chosen not to fully embrace the European model, even though the original vision for Ontario’s colleges was closer to that model to than to the American one.